Stakeholders in Assessment and Evaluation: An Analysis of Evaluation in Afghanistan and Its Effects - Ehsanullah Pamir; Asadullah Waheedi; Khaled Ahmad Habib (Randwick International of Education and Linguistics Science Journal, 2023)
At first, I want to say something about stakeholders. Stakeholders indicate one type of system or organization in which all members or participants are seen having an interest in its success. Or, stakeholder denotes on a people who work for the success of the education system in schools or other educational places. They are students, teachers, employees, principals, parents, friends, education authorities, policymakers, community leaders, and members, politicians, government test service providers, researchers/Media/Religion, organizations teacher training institutions, local business leaders and school board members. When it is selecting an assessment and evaluation, it is important to consider the needs of all the stakeholders involved. Stakeholders, or persons involved with or invested in the assessment and evaluation process, include students and test-takers, administrators, parents, teachers, instructors, and many others. The Stakeholders map shows a web of potential stakeholders. It may not be possible to meet the needs of all stakeholders in assessment and evaluation. However, it is important to plan with these groups in mind and to find an assessment and evaluation that fit best. I want to review some stakeholders in assessment and evaluation, the impact of effect and I have to analyze the evaluation systems which are followed in Afghanistan. In this study, I have mostly analyzed many evaluation methods that are popular in Afghanistan and are currently being used.